2016
DOI: 10.1016/j.anr.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Emotional Intelligence in Conflict Management Strategies of Nurses

Abstract: The study determined that nurses' emotional intelligence affects conflict management strategies. To use effective strategies in conflict management, nurses must develop emotional intelligence. Training programs on conflict management and emotional intelligence are needed to improve effective conflict management in healthcare facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
2
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 18 publications
6
90
2
18
Order By: Relevance
“…Another group of studies analysed the choice of conflict styles among nursing professionals in relation to work tenure (Al Hamdan et al., ; Başoğul & Özgür, ; Kantek & Kavla, ; Mohamed & Yousef, ; Whitworth, ). For instance, nurse managers in Jordan who had less than 10 years of work experience used the integrative style of managing conflict more than those with more than 10 years of experience (Al Hamdan et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of studies analysed the choice of conflict styles among nursing professionals in relation to work tenure (Al Hamdan et al., ; Başoğul & Özgür, ; Kantek & Kavla, ; Mohamed & Yousef, ; Whitworth, ). For instance, nurse managers in Jordan who had less than 10 years of work experience used the integrative style of managing conflict more than those with more than 10 years of experience (Al Hamdan et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study in Turkey, obliging was common among Turkish nurses with more than 20 or more years of management experience while “avoiding” was observed in nurses with 6 to 10 years of work experience (Kantek & Kavla, ). In a more recent study in Turkey, nurses who had less than 5 years of work experience reported greater use of the “integrating strategy” compared to those nurses with 6 to 10 years of work experience (Başoğul & Özgür, ). In two separate studies in Egypt and the United States, an increased year of work experience was associated with greater use of all conflict management resolution styles, except for the “avoiding style” (Mohamed & Yousef, ; Whitworth, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, not all studies reported the same direction of the relationships between emotional intelligence and conflict management styles. In their study which included 277 nurses, Başoğul and Özgür () found a positive relationship between emotional intelligence and integrative, obliging, dominating and compromising conflict management styles. Another study conducted with a sample of 568 undergraduate nursing students found that emotional intelligence was positively associated with using integrating, obliging, compromising and dominating styles, and negatively associated with using the avoiding style (Chan, Sit, & Lau, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional skills have been shown to be positively associated with nurses' motivation (Donoso, Demerouti, Garrosa Hernández, Moreno‐Jiménez, & Carmona Cobo, ; Garrosa, Moreno‐Jiménez, Rodríguez‐Muñoz, & Rodríguez‐Carvajal, ), professional development activities (Fujino, Tanaka, Yonemitsu, & Kawamoto, ) and even practice performance (Lee, Gu, & Kim, ; Rankin, ). For example, high emotional skills ensure perseverance even in the case of a first failure (Agnoli, Pittarello, Hysenbelli, & Rubaltelli, ) and facilitate conflict resolution (Ceyda Başoğul & Gönül Özgür, ). All these data suggest that emotional skills could be associated with motivation for TPE both directly and indirectly, via a higher sense of autonomy, competence and relatedness in TPE.…”
Section: Introductionmentioning
confidence: 99%